(untitled) (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2022)
Current AC-DC microgrid power management solutions have a number of technical shortcomings. When it comes to controlling the voltage of interconnected microgrids, certain current control methods are established with the primary purpose of distributing electricity among interconnected microgrids based on their loading circumstances, whereas others do not take this into account. The current systems, on the other hand, are unable to successfully pursue these objectives. In order to tackle these issues, an autonomous power management strategy is proposed, which takes into account the DC microgrid’s individual loading condition before importing power from the associated AC microgrid. Controlling DC microgrid voltage with fewer converters is possible with this method. Generators and tie-converters can be used with the proposed system because it is plug-and-play compatible. A variety of operating scenarios have been used to evaluate the effectiveness of the proposed control scheme. Researchers found that the proposed strategy successfully and independently controls the DC microgrid’s power shortfall while maintaining increased voltage resiliency.